Integrity, meritocracy and inclusiveness: Singapore's core values - TAN, Tony (Institutional Knowledge at Singapore Management University, 2018)
An interview with the seventh President of Singapore, Dr Tony Tan. The seventh President of Singapore, Dr Tony Tan, talks about the challenges and opportunities for the island-state, in this interview with Philip Zerrillo.